Model Extract, Transform dan Load (ETL) Pada Data Warehouse untuk Pelaporan Evaluasi Program Studi Berdasarkan Evaluasi Diri (EPSBED) Menggunakan Model Data Warehouse EPSBED Studi Kasus : Universitas Budi Luhur - Indra Indra; Painem Painem (Universitas Budi Luhur, 2012)
Each of study program at university in Indonesia have to report the results of academic activities for one semester to the Directorate General of Higher Education, The Ministry of National Education of Republic of Indonesia (DIKTI) through the Coordinator of Private Higher Education (KOPERTIS). The report will be used in measuring the performance of the study program for each university in Indonesia. The reporting process is known as the Study Program Evaluation Based on Self Evaluation (EPSBED).Until now data from the processing of EPSBED not yet maximized by the executive party of Budi Luhur University to become one of the reference in the field of academic decisions. For this reason the analysis of the data warehouse of EPSBED may be one of an important component to be considered in any decision-making by the executive party of Budi Luhur University. Moreover, by using the EPSBED data warehouse the process of generating report become faster in a count of minutes because the process is automated and scheduled. Early stages in the datawarehouse EPSBED are extract, transform and load (ETL). ETL is applied using the two methods which are method of Kettle and manual methods. By ETL to datawarehouse EPSBED made the withdrawal process for the preparation of data reporting EPSBED of each program of study will be faster in a matter of minutes. In addition, the process of downloading data can be done by filtering, cleansing and standardizing of data and a data type and can be developed in the schedule for the data withdrawal in a certain period of time. automatically. Thus, reporting EPSBED can be completed quickly and precisely and academic data reported EPSBED stored in the datawarehouse. Keywords : EPSBED, data warehouse, extract, transform, load, etl, University and Majoring.